RIG-I drives protective type I interferon production by glial cells in response to Neisseria meningitidis and Streptococcus pneumoniae challenge - Majithia, Krishna J.; Johnson, M. Brittany (Frontiers in Immunology, 2025)
IntroductionBacterial meningitis is a rapidly progressing and often fatal infection of the central nervous system (CNS), characterized by glial cell activation and potent neuroinflammatory responses. While Toll-like receptors have been well-characterized in CNS immunity, the contribution of cytosolic nucleic acid sensors such as retinoic acid-inducible gene I (RIG-I) remains largely undefined. Although RIG-I is classically associated with initiating antiviral responses, including type I interferon (IFN) production, emerging evidence supports its role in sensing bacterial nucleic acids. Building upon prior findings that bacterial RNA can activate RIG-I in glial cells, we sought to determine the functional contribution of RIG-I during bacterial meningitis. MethodsIn this study, we utilized primary murine and immortalized human glial cells to investigate the contribution of RIG-I-mediated responses during N. meningitidis and S. pneumoniae infection. We used immunoblot analysis and specific-capture ELISAs to quantify changes in RIG-I, interferon-stimulated genes, and type I IFN production. To assess the functional role of RIG-I during bacterial infection of glial cells, we employed both siRNA-mediated knockdown and pharmacological inhibition of RIG-I and downstream signaling, respectively. ResultsWe demonstrate that RIG-I is constitutively expressed in human and murine glial cells and is further upregulated upon bacterial infection, with protein levels varying according to both the bacterial agent and glial cell subtype. Importantly, we show that RIG-I contributes to protective type I IFN responses by glial cells, leading to the restriction of bacterial burden. Additionally, our findings suggest that type I IFN signaling via IFNAR and the resulting induction of ISGs are critical for limiting bacterial survival in glial cells. Excitingly, we have also demonstrated that we can employ RIG-I nucleic acid agonists to augment these protective responses in infected glial cells. DiscussionOur findings establish RIG-I as a key cytosolic sensor that contributes to type I IFN responses in glial cells during bacterial infection of the CNS. By promoting IFNAR-dependent ISG induction, RIG-I signaling contributes to the restriction of bacterial burden. Moreover, our ability to enhance these protective responses using RIG-I agonists highlights the therapeutic potential of targeting this pathway to promote pathogen control during bacterial meningitis.